Implementation of Academic Supervision Of School Principals as Efforts to Improve Learning Quality - Nuraeni, Ririn; Fauzi, Ahmad; Ripai, Ahmad (IAIN Syekh Nurjati Cirebon, 2020)
The role of the principal is a significant factor in improving the quality of learning, so that if the role of the principal is good the school's success will be achieved. The problem in this study is the Implementation of Academic Supervision of School Principals as an Effort to Improve Learning Quality has not been carried out optimally due to the busy schedule of principals and the readiness of teachers in receiving supervision conducted by school principals. This study aims to find out more about the Implementation of Academics Supervision of School Principals in an Effort to Improve the Quality of Learning in SDN 1 Orimalang. The method in this research is descriptive qualitative method. The subjects in this study were the principal, teachers, and TU staff. Research data obtained through observation, interviews, and documentation. Validity is done through a credibility test. Data analysis using an interactive model has four stages namely the stage of data collection, the reduction stage, the display stage, and the stage of drawing conclusions or verification. From the results of the study, it can be concluded that the Implementation of School Principal Academic Supervision as an Effort to Improve the Quality of Learning in SDN 1 Orimalang has gone well, planned, and scheduled. Academic supervision is carried out using individual and group techniques such as class visits, class observations, meetings, private conversations, seminars / workshops, and upgrading.Â Keywords: Academic Supervision, Principal, Learning Quality